The Infant Skin Barrier: Can We Preserve, Protect, and Enhance the Barrier? - Lorena S. Telofski; A. Peter Morello; M. Catherine Mack Correa; Georgios N. Stamatas (Dermatology Research and Practice)
Infant skin is different from adult in structure, function, and composition. Despite these differences, the skin barrier is competent at birth in healthy, full-term neonates. The primary focus of this paper is on the developing skin barrier in healthy, full-term neonates and infants. Additionally, a brief discussion of the properties of the skin barrier in premature neonates and infants with abnormal skin conditions (i.e., atopic dermatitis and eczema) is included. As infant skin continues to mature through the first years of life, it is important that skin care products (e.g., cleansers and emollients) are formulated appropriately. Ideally, products that are used on infants should not interfere with skin surface pH or perturb the skin barrier. For cleansers, this can be achieved by choosing the right type of surfactant, by blending surfactants, or by blending hydrophobically-modified polymers (HMPs) with surfactants to increase product mildness. Similarly, choosing the right type of oil for emollients is important. Unlike some vegetable oils, mineral oil is more stable and is not subject to oxidation and hydrolysis. Although emollients can improve the skin barrier, more studies are needed to determine the potential long-term benefits of using emollients on healthy, full-term neonates and infants.